Cytotoxic diterpenoids from the aerial parts of Scoparia dulcis. (June 2022) - Li, Yu-Peng; Wu, Dong-Xiang; Ye, Tao; Zhang, Hua
Abstract: Two formerly undescribed labdane-type diterpenoids, scoparicols C (1 ) and D (2 ), one previously unreported scopadulane-type diterpenoid 1β-hydroxydulcinodal-13-one (3 ), along with six known biogenetically related analogs (4 −9 ) were separated from the aerial parts of a traditional ethnological herb, Scoparia dulcis . Spectroscopic techniques including MS NMR and ECD were employed to characterize the structures of these molecules. While the oxidation at C-1 in 3 was reported for scopadulane-type diterpenoids for the first time, compound 7 was first obtained as a natural product in the present work. The cytotoxicity of all the isolates against four tumor cell lines (MCF-7, MDA-MB231, Hela and A549) were tested, with selective compounds showing activity in the IC50 range of 4.31–28.6 μM. Graphical Abstract: ga1 Highlights: Two new labdane and one new scopadulane diterpenoids were obtained from Scoparia dulcis . The absolute configurations were characterized by different ECD techniques. Oxidation at C-1 in compound 3 was reported for the first time for scopadulane diterpenoids. Three compounds showed cytotoxicity against all tested breast, cervical & lung tumor cells.